Institutional Pathways: Dynamics and Characteristics of System Service Use by Serious Adolescent Offenders, Arizona and Pennsylvania, 2000-2010 - Lee, JoAnn S. ([Verlag nicht ermittelbar], 2022)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigators if further information is needed. This study is a secondary analysis (syntax only, no data) of Research on Pathways to Desistance [Maricopa County, AZ and Philadelphia County, PA]: Subject Measures, 2000-2010 (ICPSR 29961) and Research on Pathways to Desistance [Maricopa County, AZ and Philadelphia County, PA]: Calendar Data, 2000-2010 [Restricted] (ICPSR 32282). The purpose of this study was to further existing knowledge of juvenile justice intervention and how juvenile justice intervention is related to positive outcomes during the transition to adulthood. This study examines three main aims using data from the Pathways to Desistance study, which followed a sample of serious adolescent offenders for seven years to examine the desistance process. First, trajectories of secure institutional placement for serious offenders during the study period were identified. Second, trajectories of gainful activities for serious adolescent offenders during the study period were identified. Gainful activities were defined as working or attending school. Third, factors associated with turning points in the gainful activities trajectories were explored. In the course of estimating the gainful activities trajectories, there appeared to be a key moment, around year 3, where multiple trajectories with moderate levels of engagement in gainful activities diverged. Together, these three aims will inform how juvenile justice intervention is related to positive outcomes during the transition to adulthood and identify factors that may be related to positive outcomes and critical turning points in the trajectories of serious adolescent offenders. Group differences were examined by testing bivariate differences in a broad range of variables: demographic variables (gender, age, and race/ethnicity); study site and year of interview; characteristics of prior service receipt at baseline (location and orientation); school, family and neighborhood characteristics; characteristics of the offense and offense history; individual factors (mental health and substance use symptoms); and risk scores.